Alemtuzumab in Multiple Sclerosis: short- and long-term effects of immunodepletion on the peripheral treg compartment - Haas, Jürgen; Würthwein, Cornelia; Korporal-Kuhnke, Mirjam; Viehöver, Andrea Maria; Jarius, Sven; Wildemann, Brigitte (Frontiers in immunology, 2019)
Treatment with alemtuzumab is followed by an early increase in Treg frequencies. Whether naïve and memory subsets are differentially affected and how depletion influences dysfunctional MS-Treg is unclear. In this study, we analyzed the effect of alemtuzumab on regulatory T-cells (Treg) in patients with multiple sclerosis (MS). For this purpose 182 blood samples from 25 MS patients were taken shortly before treatment and serially for up to 24 months after two alemtuzumab cycles. We studied Treg by flow cytometry (quantitation, phenotypical characterization), real-time polymerase chain reaction (TCR excision circles [TREC] content), CDR3-spectratyping (clonal distribution), and proliferation assays (suppressive function). CD52-mediated cytolysis of Treg and conventional T-cells was determined by a complement-dependent cytolysis assay. Our studies revealed that one week post-alemtuzumab, Treg were depicted at constant frequencies among CD4+ T-cells. In contrast, Treg frequencies were massively increased at month 1. Post-depletional Treg exhibited a CD45RO+ memory phenotype, a skewed TCR repertoire, and contained minimum TREC numbers. Naïve Treg, thymic markers, and TCR-variability commenced to rise after 6 months but did not attain baseline levels. In vitro, Treg exhibited higher susceptibility to lysis than Tcon. Treg suppressive function constantly increased within 1 year when co-cultured with syngeneic T-cells, but remained stable against allogeneic T-cells from normal donors. Our findings suggest that (1) Treg are not spared from alemtuzumab-mediated depletion and thymopoiesis does not considerably contribute to long-term recovery, (2) either homeostatic proliferation and/or conversion from residual Tcon contributes to Treg expansion during the early post-treatment phase (3) the enhanced inhibitory effect of Treg following alemtuzumab is due to altered composition and reactivity of post-depletional Tcon.
Gesehen am 16.08.2019